Force-Controlled Robotic Assembly Processes of Rigid and Flexible Objects Methodologies and Applications - Ghalyan, Ibrahim Fahad Jasim; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides comprehensive and integrated approaches for rigid and flexible object assembly. It presents comparison studies with the available force-guided robotic processes and covers contact-state modeling, scheme control strategies, and position searching algorithms. Further, it includes experimental validations for different assembly situations, including those for the assembly of industrial parts taken from the automotive industry. .
Introduction -- Contact-State Modeling -- Control of Unknown Switched-Constraints Robots -- Position Uncertainty Accommodation -- Experimental Validations -- Industrial Applications -- Conclusion and Recommendations for Future Works -- Appendices.
Keywords: Control engineering; Robotics; Automation; Manufactures; Automotive engineering; Control, Robotics, Automation; Control and Systems Theory; Machines, Tools, Processes; Automotive Engineering